2020
DOI: 10.1111/all.14292
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self‐reported and confirmed penicillin allergy in a Belgian outpatient population

Abstract: Cilostazol inhibits cytokine-induced nuclear factor-kappaB activation via AMP-activated protein kinase activation in vascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In 2017, 6.1% of patients reported an antibiotic allergy (of which 90% penicillin) at Ghent University Hospital surgical day hospitalization [ 32 ]. However, based on a prospective observational study in a Belgian outpatient population, 91% of the participants could be safely delabeled [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, 6.1% of patients reported an antibiotic allergy (of which 90% penicillin) at Ghent University Hospital surgical day hospitalization [ 32 ]. However, based on a prospective observational study in a Belgian outpatient population, 91% of the participants could be safely delabeled [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective study performed in Antwerp, Belgium, prevalence of self-reported penicillin allergy was 12%. However, it considered a population visiting the outpatients' allergy departments presumably inducing referral bias (28).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, only approximately 5% of the patients will finally be diagnosed with an IDHRs to AXE. 9 A new diagnostic test should therefore be able to offer absolute specificity to reduce the pandemic of false 'penicillin allergy'. Admittedly, accuracy is still not absolute and there is still far to go from this proof of concept to mainstream use.…”
Section: Dual Intracellular Staining Of Cd154 (Cd40l) and Cytokines A...mentioning
confidence: 99%
“…The maximal net AXE‐induced intracellular expression of CD154, IL‐4, and IFN‐γ is 0.03%, 0.25% and 0.10% respectively. Therefore, keeping in mind the low pretest probability related to the pandemic of false ‘penicillin allergy’, 9 we deemed it necessary to avoid false positive results. Hence, we fixed the decision thresholds at the upper values measured in the control individuals, keeping false positive results at 0%.…”
Section: Figurementioning
confidence: 99%